A Quality-Based Human Resource Performance Development Model in Private Higher Education: A Case Study at Muhammadiyah University of Tangerang - Dudung Hadiwijaya (Journal of Innovative and Creativity, 2026)
This study examines a quality-based human resource performance development model in private higher education, with a specific case study at Muhammadiyah University of Tangerang. The research is grounded in the growing need for private universities to strengthen human resource performance to enhance academic quality, institutional competitiveness, and stakeholder trust. The objective of this study is to analyze the design, implementation, and effectiveness of a quality-oriented performance development model for academic staff. A qualitative case study approach was employed, using data collection methods that included in-depth interviews, observations, and document analysis involving university leaders, human resource managers, and lecturers. The findings reveal that a quality-based performance development model is built upon competency standards, continuous professional development programs, measurable performance indicators, and integrated quality assurance mechanisms. Key supporting factors include leadership commitment, structured evaluation systems, and training aligned with institutional quality targets. The model contributes to improvements in teaching effectiveness, research productivity, and academic service. The study concludes that integrating quality assurance principles into human resource performance development provides a sustainable framework for strengthening lecturer performance in private higher education institutions.